Industrial Voluntarism in Canada - Tucker, Sean; Mucalov, Alex (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2010)
The term “industrial voluntarism” has been used to describe the norm that dominated union organizing and, more broadly, union-management relations in Canada during most of the first half of the 20th century. In practical terms, the principle defines situations in which unions and employers initiate, develop, and enforce agreements without state assistance or compulsion. This paper investigates the history of voluntarism in Canada with attention to post-war legal accommodations and various manifestations of voluntarism related to union recognition. We show how aspects of the Framework of Fairness Agreement (FFA) negotiated between Magna International and the Canadian Auto Workers (CAW) in 2007 is informed by industrial voluntarism. The FFA facilitates voluntary recognition of CAW locals at Magna plants in exchange for a no-strike promise and acceptance of many features of Magna’s existing human resource management system. Overall, the historical and contemporary evidence show that voluntarism continues to manifest in different forms in response to changing labour relations conditions.